Developing Theoretic Strategies of Sharing Corporate Social Responsibility Conduct in a Closed-loop Supply Chain System - Jonas C.P. Yu (International Journal of Supply Chain Management, 2018)
Due to the environmental impacts and economic benefits, establishment of business strategies for sustainable development is getting increasing attention both in industry as well as in academia. In order to improve the coporate social responsibility (CSR), we develop an Extend Producer Responsibility (EPR) model which refers to original equipment manufacturer (OEM) takeback in a closed-loop supply chain system under incentive-dependent demand and return. The performance analysis of the system dynamics simulation model will indicate that the inclusion of incentive offer enhances the demand, collection and remanufacturing process. A numerical example and sensitivity analysis on the optimal results are presented to validate the proposed model.